1982
DOI: 10.1002/dev.420150105
|View full text |Cite
|
Sign up to set email alerts
|

Motor asymmetries in preterm infants: Effects of prematurity and illness

Abstract: Two types of motor asymmetry, postural asymmetry and lateral head turning, were assessed in 3 groups of preterm infants, one of which had experienced respiratory distress syndrome (RDS) in the postnatal period. Results reveal that maintenance of a right postural asymmetry is present as early as 34 weeks conceptional age and is not disrupted by postnatal illness. Lateral head turning after midline placement was evident as early as 36 weeks conceptional age but was disrupted by physiologic condition. Infants who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
(16 reference statements)
2
11
1
1
Order By: Relevance
“…During the maintenance of a lateralized head position, the contralateral sternocleidomastoid muscle is much more active than its ipsilateral homologue, a difference which was not found for the trapezius muscle (Bakker & Prechtl, 1980). A higher susceptibility to risk factors for assumption as opposed to maintenance was reported previously in a study on preterm infants before term age by Fox and Lewis (1982). They found more left-sided turns in infants with IRDS.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…During the maintenance of a lateralized head position, the contralateral sternocleidomastoid muscle is much more active than its ipsilateral homologue, a difference which was not found for the trapezius muscle (Bakker & Prechtl, 1980). A higher susceptibility to risk factors for assumption as opposed to maintenance was reported previously in a study on preterm infants before term age by Fox and Lewis (1982). They found more left-sided turns in infants with IRDS.…”
Section: Discussionmentioning
confidence: 48%
“…Previously, Fox and Lewis (1982) demonstrated that preterm birth did not adversely affect the maintenance of a lateral head position. They observed a consistent rightsided preference at 34 weeks postmenstrual age (PMA).…”
Section: Introductionmentioning
confidence: 98%
“…Nor has the disorganization hypothesis beensupported consistently in direct comparisons of healthy and at-risk newborns. For example, Fox and Lewis (1982) studied healthy full-term infants, healthy preterm infants, and premature infants who had perinatal medical complications and did not find the percentage of head-left position to be higher in the at-risk group.…”
mentioning
confidence: 99%
“…Fox and Lewis (1982) found that preterm infants who had undergone respiratory distress syndrome did not exhibit a right turning bias. Lewkowicz, Gardner, and Turkewitz (1979) also found that the right turning bias was affected by preterm birth.…”
mentioning
confidence: 99%